Long-run impact of coal usage decline on CO2 emissions and economic growth: Evidence from disaggregated energy consumption perspective for China and India by dynamic ARDL simulations - Kartal, Mustafa Tevfik; Depren, Serpil Kilic; Ali, Uzair; Nurgazina, Zhanar (SAGE PUBLICATIONS LTD, 2024)
This study examines the long-run impact of coal usage decline from a disaggregated energy consumption perspective by considering the role of coal usage on carbon dioxide (CO2) emissions and economic growth. For this purpose, the study focuses on China and India as the leading coal-user countries; considers coal, oil, natural gas, and renewable energy consumption as explanatory variables; uses yearly data from 1990 to 2021, and applies a novel dynamic autoregressive distributed lag (DYNARDL) simulations. Also, the Kernel-based regularized least squares (KRLS) approach is performed for robustness checks. The outcomes show that (i) there is cointegration between coal usage and CO2 emissions, and between coal usage and economic growth in the long run; (ii) coal usage is the most important indicator among explanatory variables; (iii) coal usage has a statistically significant impact on CO2 emissions in both China and India; (iv) however, coal usage is not significantly effective on economic growth for both China and India based on DYNARDL simulations; (v) negative counterfactual shocks in coal usage have a decreasing impact on CO2 emissions; (vi) KRLS results show that coal usage has a causal impact on CO2 emissions and the results of the DYNARDL simulations are robust. Hence, counterfactual shocks present important insights about the future impacts of coal usage decline on both CO2 emissions and economic growth. Based on the empirical results, policy implications, such as decreasing the amount of coal usage on and increasing the amount of alternative energy sources in the total energy mix, are also proposed.
Keywords: Coal; CO2 emissions; economic growth; DYNARDL; KRLS; China and India; HYPOTHESIS; Environmental Sciences & Ecology